Cumulative diameter growth and biological rotation age for seven tree species in the Cerrado biogeographical province of Bolivia - Lopez Callejas, Lidio (2013)
In this contribution we document the radial growth rates of seven tropical species largely used for timbers in the Bolivian Cerrado, the region with the largest wood production in Bolivia. Inter-annual variations in tree-ring widths were measured on cross-sections from Amburana cearensis, Cedrela fissilis, Platimiscium ulei, Centrolobium microchaete, Hymenaea courbaril, Anadenanthera colubrina and Ficus boliviana. For a common period of 100 years, the mean annual diametric growth ranged from 0.55 to 1.05 cm year1 in Platimiscium ulei and Ficus boliviana, respectively. Mean cumulative variations in diameter growth of Centrolobium microchaete at six different sites ranged from 32.7 to 38.6 cm over a 100-year period. Variations in tree ages to reach the minimum cutting diameter (MCD) of 40 cm in the Chiquitano district ranged from 32 to >140 years, whereas in the Guarayos district (MCD = 50 cm) from 38 to 140 years. For Centrolobium microchaete, temporal variations for reaching the MCD ranged from 35 to 140 years and from 45 to 110 years for the Chiquitano and Guarayos districts, respectively. Since large differences in cumulative diametric growth were recorded between species and between sites for the same species, difference in growth rates between species and sites should be taken into consideration to ensure sustainable forest management in tropical dry forests. Biological rotation ages, estimated on the temporal evolution of the mean and current annual basal area, occur at ages over 80 years for most selected species. This information has significant implications for the management of the forests and suggests that the current cutting cycles of 20 years greatly overestimate the growth rate of tree species in the Boliviano Cerrado forest.